Pengaruh Kerjasama Tim, Kompensasi, dan Kepuasan Kerja Terhadap Keterlibatan Karyawan pada PT. Golden Tekstil Indonesia - Khairunnisa, Syalsabilla Fajar; Fauzan, Mohammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze and explain (1) the effect of teamwork on employee engagement, (2) the effect of compensation on employee engagement, and (3) the effect of job satisfaction on employee engagement at PT. Golden Textile Indonesia. This type of research is explanatory research. The research sample is employees of PT. Golden Textile Indonesia has 100 employees. Data collection uses a questionnaire using a google form, which is then sent to respondents. Data processing and analysis using SPSS version 29. The findings of the study show that (1) Teamwork has no effect on employee engagement; (2) compensation has a positive effect on employee engagement; (3) Job satisfaction has a positive effect on employee involvement in PT. Golden Textile Indonesia.